2010
DOI: 10.1111/j.1469-8986.2010.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Resonances in the cardiovascular system caused by rhythmical muscle tension

Abstract: Paced 0.1 Hz breathing causes high amplitude HR oscillation, triggering resonance in the cardiovascular system (CVS). This oscillation is considered to be a primary therapeutic factor in HRV biofeedback treatments. This study examined whether rhythmical skeletal muscle tension (RSMT) can also cause 0.1 Hz resonance in the CVS, and compared oscillatory reactivity in CVS functions caused by RSMT and paced breathing (PB). Sixteen young healthy participants completed five tasks: baseline, three RSMT tasks at frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 55 publications
2
41
0
Order By: Relevance
“…Resonance is an occurrence in which an oscillation at a specific frequency appears in a system in response to perturbation (Vaschillo, Vaschillo, Pandina, & Bates, ). This principle has been applied to the cardiovascular (CV) system through the use of paced respiration at 6 breaths per min (i.e., 0.1 Hz, a dominant resonant frequency in the CV system), which produces cardiovascular resonance (i.e., large fluctuations in heart rate and blood pressure).…”
Section: Cardiovascular Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…Resonance is an occurrence in which an oscillation at a specific frequency appears in a system in response to perturbation (Vaschillo, Vaschillo, Pandina, & Bates, ). This principle has been applied to the cardiovascular (CV) system through the use of paced respiration at 6 breaths per min (i.e., 0.1 Hz, a dominant resonant frequency in the CV system), which produces cardiovascular resonance (i.e., large fluctuations in heart rate and blood pressure).…”
Section: Cardiovascular Resonancementioning
confidence: 99%
“…The 0.1 Hz resonant frequency of the CV system is thought to be due to the mechanisms of the arterial baroreflex (Vaschillo, Lehrer, Rishe, & Konstantinov, ; Vaschillo et al., ). Treatments that utilize paced breathing to amplify 0.1 Hz oscillations in heart rate and blood pressure have been shown to strengthen the baroreflex system (Lehrer et al., ).…”
Section: Cardiovascular Resonancementioning
confidence: 99%
“…Less recognized and understood, concurrent evidence also suggests that voluntary rhythmic muscle contraction alone could be an alternative way of stimulating the parasympathetic nervous system. In a study on rhythmic contraction alone, Lehrer et al demonstrated that when large muscle groups alternated rhythmically between contraction and relaxation, subjects experienced a similar parasympathetic entrainment effect observed in the earlier paced breathing studies (Lehrer, Vaschillo, Trost, & France, ; Vaschillo, Vaschillo, Pandina, & Bates, ). However, the autonomic effects of performing rhythmic synchronized breathing and muscle contraction tasks simultaneously have not been studied systematically.…”
Section: Introductionmentioning
confidence: 72%
“…In this type of modeling, although relatively good matching between modeled and measured output heart rate values was achieved, it is difficult to relate transfer function parameters to actual physiological mechanisms underlying the phenomenon. Moreover, by calculating transfer functions between respiratory and heart rate signals, one can obtain useful information about resonance effects (Ahmed et al, 1986;Vaschillo et al, 2002Vaschillo et al, , 2011. In fact, transfer functions can be formally calculated for a wide variety of physiological or other type of signals, allowing the reconstruction of the output based on previous samples of input as well as of output.…”
Section: Discussionmentioning
confidence: 98%